Translation Technique of English to Indonesian Subtitle in “Crazy Rich Asian” Movie - Tira Nur Fitria (Hasanuddin University, 2020)
This objective of the research is to classify the types of translation technique from English to Indonesian subtitle, to determine the most dominant type of translation technique of English to Indonesian subtitle of “Crazy Rich Asian” movie. This research is descriptive qualitative research. It presents the problem clearly based on the most accurate data, explaining and describing the topic of a problem based on the theory used. The technique of collecting data used is documentation. There are 8 types of translation techniques found in the subtitle Crazy Rich Asian movie. The type of translation techniques used are Shift/Transposition as 72 data or 19.46 %, Literal as 70 data or 18.92 %, Established Equivalence as 62 data or 16.76 %, Reduction/Omission as 53 data or 14.32 %, Borrowing as 52 data or 14.05 %, Addition/Amplification as 30 data or 8.11 %, Modulation as 26 data or 7.03 % and Adaptation as 5 data or 1.35 %. While the most dominant type of translation technique of English to Indonesian subtitle of “Crazy Rich Asian” movie is shift/transposition.